Will Radiation-Induced Bystander Effects or Adaptive Responses Impact on the Shape of the Dose Response Relationships at Low Doses of Ionizing Radiation? - William F. Morgan (SAGE Publishing, 2006)
Radiation induced bystander effects and adaptive responses are two phenomena that modulate cellular responses to low doses of ionizing radiation. Bystander effects generally exaggerate the effects of low doses of radiation by eliciting detrimental effects in non-irradiated cells, thus making the target for radiation effects greater than the volume irradiated. Adaptive responses on the other hand indicate that low doses of radiation can reduce damage induced by a second challenging dose. The potential impact of these two low dose effects on the shape of the dose response relationship will be discussed.